GREEN CONCEPTS AND MATERIAL FLOW COST ACCOUNTING APPLICATION FOR COMPANY SUSTAINABILITY - Marota, Rochman (Indonesian Journal of Business and Entrepreneurship, 2017)
Health equipment and furniture become a complementary factor for good health services to the communities. Management of health equipment and furniture is started by manufacturers within the industry scope and sustainable business processes. This study aimed to apply green concepts and MFCA at PT XYZ, and to analyze their effects on the dimensions of the company sustainability. To measure the effects of green concepts and MFCA on the dimensions of corporate sustainability, a multiple regression analysis was used. The analysis showed that they gave significant effects from the results of the F test, t test and probability test. From these results, a number of suggestions for improvement of production process performance as managerial implications for maintaining the stability of the company sustainability index were formulated.Keywords: efficiency and effectiveness of production cost, green concepts, the company sustainability, material flow cost accounting